Production of high-quality biogenic fuels by co-pelletization of sugarcane bagasse with pinewood sawdust and peanut shell - de Almeida Moreira, Bruno Rafael [UNESP]; Barbosa Júnior, Marcelo Rodrigues [UNESP]; de Brito Filho, Armando Lopes [UNESP]; da Silva, Rouverson Pereira [UNESP] (Springer Nature, 2022)
Sugar-energy sector is key to the provision of food and energy worldwide. However, it can largely generate mill-run bagasse as an agro-residual biomass. The tradition of the sector is to put it back into the industrial process as an alternative fuel to co-generate steam and power for milling and biorefining factories. However, excessive ash in the mineral phase of this material typically makes it challenging for burning it in boilers cost-effectively, driving the need of developing a more suitable pathway for its disposal. Therefore, the objective of this study was to analyze whether co-pelleting sugarcane bagasse with either pinewood sawdust or peanut shell could make it possible for transforming this low-technical-quality agro-residual biomass into a solid biofuel of superior quality. The production of pellets consisted of co-pressing sugarcane bagasse with either pinewood sawdust or peanut shell at the standard proportion of 50/50 on an automatic pelletizer at 200 MPa and 125°C. The blending improved the quality of biopellets. These products fulfilled the requirements of European standards for premium-grade solid biofuels. Blends proved to be highly energetic (15.1–15.35 GJ m−3) and durable (98.05–98.7%). They also emitted less of NOx (92.7–101.55 mg m−3), CO (59.05–63.2 mg m−3), and volatile organics (26.3–29.65 mg m−3), making it possible for the boiler to operate a clearer and safer way. Therefore, insights into the conceptual and technical ramifications of this study can provide further knowledge to progress the field’s prominence in transforming sugarcane bagasse into a solid biofuel of greater quality.
Keywords: Agro-industrial residue; Biomass; Blend; Emission; Solid biofuel; Waste-to-energy pathway